Объяснение:
1) Преобразуем в многочлен:
а) (у - 4) ² = y ^ 2 - 2 * y * 4 + 4 ^ 2 = y ^ 2 - 8 * y + 16;
б) (7 * х + а) ² = 49 * x ^ 2 + 14 * x * a + a ^ 2;
в) (5 * с - 1) * (5 * с + 1) = 25 * c ^ 2 - 1;
г) (3 * а + 2 * b) * (3 * а - 2 * b) = 9 * a ^ 2 - 4 * b ^ 2;
2) У выражение:
(а - 9) ² - (81 + 2 * а) = a ^ 2 - 18 * a + 81 - 81 - 2 * a = a ^ 2 - 20 * a = a * (a - 20);
3) Разложиv на множители:
а) х ² - 49 = (x - 7) * (x + 7);
б) 25 * х² - 10 * х * у + у ² = (5 * x) ^ 2 - 2 * (5 * x) * y + y ^ 2 = (5 * x - y) ^ 2.
x=4
Объяснение:
{x+y=−5 {x+y=−5
=> + => 2x=8
x−y=14 x−y=14 x=4